BONE MINERAL DENSITY IN PATIENTS WITH CHRONIC LOW BACK PAIN: Bone Mineral Density - Aziz, Tariq; Jilani, Saira; Khan, Atif Ahmed; Ahmad, Mahmood; Iqbal, Sara; Shafaat, Hina Kanwal (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine mean bone mineral density in patients with chronic low back pain presenting at ArmedForces Institute of Rehabilitation Medicine Rawalpindi based on dual energy x-ray absorptiometry studies.Study Design: Cross sectional study.Place and Duration of Study: Armed Forces Institute of Rehabilitation Medicine (AFIRM), Rawalpindi from Apr2015 to Mar 2016.Patients and Methods: Two hundred and forty patients having low back pain of more than 6 months durationfulfilling the inclusion criteria were included both from indoor and outdoor departments through non-probabilityconsecutive sampling. Bone mineral density was measured at lumbar spine by dual energy x-ray absorptiometrystudies by the same technical staff using the same equipment. A written informed consent was taken from eachpatient. Data were collected and recorded on specialized proforma by the principal investigator.Results: Spine BMD on DXA scan ranged from 0.90 to 0.98 g/cm2 with a mean of 0.95 ± 0.02 as shown in. Whenstratified, the mean BMD decreased significantly with increasing age and severity of LBP; 20-30 years vs. 31-40years (0.95 ± 0.01 vs. 0.92 ± 0.02; p=0.001). However, there was no significant difference in mean BMD acrossgenders; male vs. female (0.94 ± 0.01 vs. 0.94 ± 0.02; p=0.680). Similarly there was no significant difference in meanBMD across various durations of low back pain; 7-10 vs. 11-14 months (0.94 ± 0.03 vs. 0.93 ± 0.01; p=0.617).Conclusion: The mean bone mineral density at spine was found to be lower in patients with chronic low backpain. It was significantly lower in older patients and those with severe low back pain. However, it didn’t changesignificantly with various durations of low back pain or gender.